Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/21870764.2020.1793876
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Li1.3Al0.3Ti1.7(PO4)3 solid electrolyte via a sol-gel method using various Ti sources

Abstract: In this study, LATP (Li 1.3 Al 0.3 Ti 1.7 (PO 4) 3) solid electrolyte is prepared by a sol-gel process using Ti(C 2 H 5 O) 4 , Ti(n-C 3 H 7 O) 4 and Ti(n-C 4 H 9 O) 4 as Ti sources to examine the influence of the Ti source on the electrochemical properties of produced LATP. LATP is successfully produced in all cases, however, AlPO 4 impurity is formed in the Ti(n-C 3 H 7 O) 4 and Ti(n-C 4 H 9 O) 4 samples due to insufficient formation of Ti-O-Al network. In contrast, the AlPO 4 formation is not observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…23−25 In contrast, without sintering aids, the previous study reported an ionic conductivity of only 0.38 mS/cm for LATP at a sintering temperature of 1080 °C. 26 However, based on our insights from the above-mentioned reports, we find that these articles have omitted some important points that are crucial for laboratory preparation and the commercial manufacture of high-performance LATP solid electrolytes: (1) most researchers only investigate the effects of one or two important factors in their own studies, neglecting to discuss some other key parameters, 14,18 which may make it difficult for readers to replicate their results, and (2) too many articles focus on the influencing mechanism of individual process parameters, but none of them systematically and deeply discuss the relationship and interactions of these factors. 17,27 Although studying the effects of a certain synthesis factor is important and necessary, it is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23−25 In contrast, without sintering aids, the previous study reported an ionic conductivity of only 0.38 mS/cm for LATP at a sintering temperature of 1080 °C. 26 However, based on our insights from the above-mentioned reports, we find that these articles have omitted some important points that are crucial for laboratory preparation and the commercial manufacture of high-performance LATP solid electrolytes: (1) most researchers only investigate the effects of one or two important factors in their own studies, neglecting to discuss some other key parameters, 14,18 which may make it difficult for readers to replicate their results, and (2) too many articles focus on the influencing mechanism of individual process parameters, but none of them systematically and deeply discuss the relationship and interactions of these factors. 17,27 Although studying the effects of a certain synthesis factor is important and necessary, it is not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on our insights from the above-mentioned reports, we find that these articles have omitted some important points that are crucial for laboratory preparation and the commercial manufacture of high-performance LATP solid electrolytes: (1) most researchers only investigate the effects of one or two important factors in their own studies, neglecting to discuss some other key parameters, , which may make it difficult for readers to replicate their results, and (2) too many articles focus on the influencing mechanism of individual process parameters, but none of them systematically and deeply discuss the relationship and interactions of these factors. , Although studying the effects of a certain synthesis factor is important and necessary, it is not sufficient. Systematic research on the relative importance and the interactions amongst each of the important factors is also essential and can help us directly and effectively comprehend the whole preparation of LATP pellets from a new perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Depending on heat treatment temperature, this procedure avoids the appearance of secondary phases after the NASICON crystallization that could block the lithium-ion motion. 44 Moreover, this technique is a simple strategy to produce specimens with complex shapes and with efficient microstructural control through crystallization. 42,43 Once robust setups for the parent glass preparation and further crystallization are usually not required, glass ceramic technology is a promising scale-up technique for NASICON preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a vast body of literature on the production of NASICONs such as glass ceramics to obtain solid electrolytes. ,,, The homogeneous melts provided by the preparation of the parent glass provide a high degree of compositional control . Depending on heat treatment temperature, this procedure avoids the appearance of secondary phases after the NASICON crystallization that could block the lithium-ion motion . Moreover, this technique is a simple strategy to produce specimens with complex shapes and with efficient microstructural control through crystallization. , Once robust setups for the parent glass preparation and further crystallization are usually not required, glass ceramic technology is a promising scale-up technique for NASICON preparation.…”
Section: Introductionmentioning
confidence: 99%